2016
DOI: 10.19173/irrodl.v17i3.2274
|View full text |Cite
|
Sign up to set email alerts
|

Flipped Classroom Research and Trends from Different Fields of Study

Abstract: This paper aims to analyse the trends and contents of flipped classroom research based on 20 articles that report on flipped learning classroom initiatives from 2013-2015. The content analysis was used as a methodology to investigate methodologies, area of studies, technology tools or online platforms, the most frequently keywords used and works cited references, impacts for students' learning, and flipped classroom challenges. The results of the analysis were interpreted using descriptive analysis, percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
171
0
29

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 316 publications
(258 citation statements)
references
References 53 publications
(114 reference statements)
11
171
0
29
Order By: Relevance
“…Moreover, we also found that the data analysis techniques of the studies had not been analyzed in former research (e.g. Zainuddin & Halili, 2016;Aydin & Demirer, 2017;Sakar & Sagir, 2017;Yildiz et al, 2017).…”
Section: Discussion and Future Implicationsmentioning
confidence: 90%
See 4 more Smart Citations
“…Moreover, we also found that the data analysis techniques of the studies had not been analyzed in former research (e.g. Zainuddin & Halili, 2016;Aydin & Demirer, 2017;Sakar & Sagir, 2017;Yildiz et al, 2017).…”
Section: Discussion and Future Implicationsmentioning
confidence: 90%
“…This tendency is not consistent with other content analysis studies. In both Zainuddin and Halili (2016) and Aydin and Demirer's (2017) studies, the most frequently used methodologies in flipped classroom research were the mixed-method approach (quantitative and qualitative), followed by the quantitative approach.…”
Section: Discussion and Future Implicationsmentioning
confidence: 99%
See 3 more Smart Citations